The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3389/feduc.2023.1106679
|View full text |Cite|
|
Sign up to set email alerts
|

Artificial neural network model to predict student performance using nonpersonal information

Abstract: In recent years, artificial intelligence has played an important role in education, wherein one of the most commonly used applications is forecasting students’ academic performance based on personal information such as social status, income, address, etc. This study proposes and develops an artificial neural network model capable of determining whether a student will pass a certain class without using personal or sensitive information that may compromise student privacy. For model training, we used information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In Addition, ref. [29] developed an artificial neural network designed to predict a student's likelihood of passing a specific course, importantly, without relying on personal or sensitive information that could infringe on student privacy. The model was trained using data from 32,000 students at The Open University in the United Kingdom, incorporating details such as the number of attempts at the course, the average number of assessments, the course pass rate, the average engagement with online materials, and the total number of clicks within the virtual learning environment.…”
Section: Related Workmentioning
confidence: 99%
“…In Addition, ref. [29] developed an artificial neural network designed to predict a student's likelihood of passing a specific course, importantly, without relying on personal or sensitive information that could infringe on student privacy. The model was trained using data from 32,000 students at The Open University in the United Kingdom, incorporating details such as the number of attempts at the course, the average number of assessments, the course pass rate, the average engagement with online materials, and the total number of clicks within the virtual learning environment.…”
Section: Related Workmentioning
confidence: 99%
“…Heyul Chavez et al [3] predicted students' academic performance using ANN. The system used the Open University of the United Kingdom dataset, which contains 32,000 student's data.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many ML methods are used to forecast student performance in online courses, including Random Forest (RF), Support Vector Machine (SVM), Naive Bayes (NB), and Logistic Regression (LR). It generates two sorts of output: pass, the learner will complete the course successfully, and fail, the learner might not [3]. Teachers can gain a better grasp of their data by utilizing ML techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Another encouraging work on the development of a suitable neural network model to accurately predict the probability that a student will pass an examination can be seen to have used ten characteristic attributes as the input variables for a three-layer ANN (11) . The said model has no need to infringe students' personal information, but has successfully demonstrated that the ANN model is superior to Naïve Bayes algorithm, Decision trees/random forests or Support vector machine (SVM)/support vector regression (SVR) in terms of ability to predict the academic performance of students at 83% accuracy level.…”
Section: Artificial Neural Network (Ann)mentioning
confidence: 99%